2021
DOI: 10.26874/jakw.v2i2.138
|View full text |Cite
|
Sign up to set email alerts
|

Using Youtube as a Learning Tool for Basic Volleyball Techniques for Junior High School Students during Pandemic

Abstract: Pandemi COVID-19 berdampak besar pada pendidikan di Indonesia. Berbagai upaya dilakukan untuk menarik minat belajar siswa, salah satu upaya yang dilakukan guru adalah video pembelajaran dengan tujuan agar siswa dapat memahami pelajaran dengan baik. Tujuan dari kegiatan ini adalah untuk mengetahui efektivitas aplikasi Youtube sebagai sarana pembelajaran olahraga bagi siswa SMP di masa pandemi. Hasil data kegiatan ini menunjukkan diperoleh 52% hasil pretest pengetahuan teknik dasar bola voli siswa. Namun setelah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Live sports learning involves both a personal investment of time and energy, and may also include a personal financial investment of monetary expenditures. College students are enthusiastic about participating in live sports learning and personally invest time and energy in online learning to gain knowledge about sports skills and physical activity [12][13][14][15][16][17]. Therefore, participation in live sports learning effectively enhances their loyalty to sports activities [28].…”
Section: Relationship Between Live Sports Learning and Exercise Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Live sports learning involves both a personal investment of time and energy, and may also include a personal financial investment of monetary expenditures. College students are enthusiastic about participating in live sports learning and personally invest time and energy in online learning to gain knowledge about sports skills and physical activity [12][13][14][15][16][17]. Therefore, participation in live sports learning effectively enhances their loyalty to sports activities [28].…”
Section: Relationship Between Live Sports Learning and Exercise Behaviormentioning
confidence: 99%
“…2024, 14, 266 2 of 14 more effective than traditional learning methods in enhancing users' sports skills and fostering interest in achieving learning outcomes [8]. Studies have shown that videos about the technical abilities used in soccer [12], football [13], and volleyball [14] are receiving much attention from participants. Additionally, live sports streaming provides access to professional sports competitions [15], team analysis [16], and relevant knowledge about sports injury treatment [17].…”
Section: Introductionmentioning
confidence: 99%